The influence of psychological distance and topic type on inter-brain synchronization of emotion perception during face-to-face communication: an fNIRS hyperscanning study - Tao, Yun; Zhou, Meng; Wang, Jiayin; Li, Xuzhou; Ma, Xie (Frontiers in Neuroscience, 2025)
Emotional perception plays a crucial role in social interaction; however, previous studies have majorly focused on static emotion perception rather than examining how emotions unfold during communication. Therefore, this study investigated how psychological distance (friends vs. stranger pairs) and topic type (shared vs. exclusive experiences) modulate inter-brain synchronization (IBS) during emotional communication, using functional near-infrared spectroscopy (fNIRS). The results showed that: (1) shared story (vs. exclusive story) elicited higher levels of emotion perception, both for self and other (p < 0.05), and friends (vs. stranger) perceived their friends’ negative emotions more strongly (p < 0.05). (2) Higher IBS was observed at the right superior frontal gyrus (rSFG; BA 10) when shared story in friend than shared story in stranger (p_FWE < 0.05). The results indicate that with the deepening of friendships, the overlap between the two parties increases, resulting in higher emotional resonance when sharing common experiences. These findings provide brain imaging evidence supporting the involvement of emotion perception during communication.